Bioavailability of phenolic compounds and redox state of murine liver and kidney as sex-dependent responses to phytoextracts - Albrecht, Claudia (2017)
Plant extracts can be obtained to carry bioactive compounds, useful for prevention and treatment of different illnesses. This also supports the intake of teas as functional beverages. Nonetheless, it is incompletely known whether these extracts can act as effective sources and vehicles de phenolic compounds (phenolics/polyphenols) to reach their targets. Objective: To establish whether phytoextract ingestion modified in a sex-dependent manner the phenolic bioavailability and redox response in liver and kidney. Method: BALB/C mice ingested for a month 100 mg/Kg/d of extracts (tea-like) from Aspidosperma quebracho-blanco (AQB), Lantana grisebachii (LG) or Ilex paraguariensis (IP). Then, phenolics, peroxides and nitrites were analyzed by spectrophotometry. Also, phenolic permeation from digested and undigested extracts was evaluated in vitro with a rat jejunum-based assay. Results: Phenolic permeation depended on extract digestion. In males, IP showed a special time course of hepatic phenolics, whereas all extracts decreased renal phenolics at 15 days. Extracts induced hepatic lipoperoxides at 15 days. LG reduced renal hydroperoxides at 15 days and hepatic nitrites at 30 days, whereas AQB and IP reduced renal lipoperoxides and nitrites at 30 days. In females, extracts reduced hydroperoxides, with LG and AQB also reducing lipoperoxides. IP increased renal lipoperoxides at 30 days. Conclusion: IP was a relevant phenolic source. Sex-dependent responses were found in all variables, which should be considered to prevent misleading generalizations in phytodrug bioprospecting.